Batik Bogor Tradisiku: Kajian Strukturalisme Genetis dan Memetis - Wijayanto, Eko (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2013)
Batik Bogor Tradisiku might be seen as an innovation by the couple Siswaya-Rukoyah. This batik is a variant of the Javanese Batik as the creator habitus. Tradisiku may be considered a particular social ‘action’ especially due to its tendency to create and develop its own distinction. This paper is inspired by Pierre Bourdieu’s genetic structuralism to read and interpret the scheme of perception and the social action of the actors in producing the Batik Bogor. In the meantime, the approach of memetics introduced by the biologist Richard Dawkins is used to interpret the Batik Bogor as a meme, the smallest cultural information unit that spreads out through the social cognition process. The role of the agent will be considered as a vector, not an actor.